2001
DOI: 10.1176/appi.ps.52.7.959
|View full text |Cite
|
Sign up to set email alerts
|

Trauma, Symptoms of Posttraumatic Stress Disorder, and Associated Problems Among Incarcerated Veterans

Abstract: The findings encourage the development of an improved treatment model to keep jailed veterans with PTSD from repeated incarceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 24 publications
5
89
1
1
Order By: Relevance
“…Although, it is impossible to tell from the data the degree to which the mental illnesses found among veterans in the samples were associated with combat exposure, this finding is consistent with past research which suggests that mental illnesses resulting from combat exposure may increase veterans risk of incarceration [20,21,23,29]. We lacked data on substance abuse, which is likely to be a highly significant unmeasured risk factor for incarceration, since new drug laws sharply increased the risk of incarceration related to drug use [53][54][55].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although, it is impossible to tell from the data the degree to which the mental illnesses found among veterans in the samples were associated with combat exposure, this finding is consistent with past research which suggests that mental illnesses resulting from combat exposure may increase veterans risk of incarceration [20,21,23,29]. We lacked data on substance abuse, which is likely to be a highly significant unmeasured risk factor for incarceration, since new drug laws sharply increased the risk of incarceration related to drug use [53][54][55].…”
Section: Discussionsupporting
confidence: 87%
“…Mental illness can be a risk factor for incarceration mediated by resultant, poverty, social isolation, and anti-social behavioral dyscontrol [39][40][41][42]. More specifically, as mentioned in the introduction, mental illnesses related to combat exposure, such as Post Traumatic Stress Disorder (PTSD) has been reported to put veterans at increased risk for incarceration [17,20,21,23,29]. A dichotomous indicator of whether the veteran had a physical disability was coded as one in both data sets if the veteran reported that they had any disabling health condition.…”
Section: Health Statusmentioning
confidence: 99%
“…Some recent research has suggested that trauma and combat exposure, PTSD symptoms, substance abuse, and post deployment adjustment problems may be positive predictors of incarceration for veterans (e.g., supportive of the Violent Veteran Model; McGuire et al, 2003;Saxon et al, 2001;Yager, Laufer, & Gallops, 1984). More generally, Abramson (1972) and others have argued that the "criminalization" of mental illness has resulted in jails and prisons becoming the primary housing facilities for the mentally ill (see also Teplin, 1983Teplin, , 1984Teplin, , 1985, which would include veterans suffering from such problems.…”
Section: The Link Between Military Service Combat-related Problems Amentioning
confidence: 99%
“…Studies also support onset of addiction as a significant predictor of a history of CT when combat-related PTSD has been diagnosed. 35,36) Childhood trauma+combat-exposure→PTSD addiction These studies suggest delayed onset of addiction that is triggered by additional insult to the RegP leading to PTSD, that perhaps overloaded remaining resiliency traits that had previously defended the RewP. Readily available addictive substances and/or environmental cueing (other veterans using) were likely contributing factors to initiation of addictive substances.…”
Section: Childhood Trauma and The Regulatory And Reward Pathwaysmentioning
confidence: 97%